Potential of Citrullus lanatus seeds as a natural coagulant in drinking water treatment - Carrasquero, Sedolfo; Díaz, Altamira; Pire, María (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Natural coagulants have received significant attention due to their biodegradable nature, cost-effectiveness, and abundance of sources. The objective of the research was to analyze the efficiency of Citrullus lanatus seeds treating synthetic waters with three levels of initial turbidity (13, 75, and 200 NTU), applying four rapid mixing times (1, 2, 4, and 5 min) in the purification process. The coagulant was prepared with 5 g of the seed previously ground, sieved, defatted, and diluted in a volume of 1 L of distilled water. Jar tests were performed using doses of 50, 70, 90, 100, 150, 200, 250, 300, 400, and 500 mg.L-1 using true color and turbidity as control parameters. The coagulation was performed at a speed of 100 rpm, while flocculation lasted 20 minutes at 30 rpm, and the resting phase was 30 minutes. It was obtained that the optimal doses of C. lanatus in the treatment process were 50, 150, and 300 mg. L-1 for waters with 13, 75 and 200 NTU, respectively, obtaining the highest percentages of turbidity removal (96.6%) and true color (94.4%) in water with 75 NTU. Furthermore, it was concluded that increasing the time in the rapid mixing phase caused an increase in the levels of turbidity and true color; being the time of 2 min the one that generated water that meet the values desired by the current Venezuelan drinking water regulations, which contemplates 1 NTU for turbidity and 5 UC Pt-Co for true color.